PENGARUH MOTIVASI KERJA, PENGALAMAN KERJA DAN PELATIHAN TERHADAP KINERJA GURU DI SMK KESEHATAN BALI DEWATA - Ni Luh Putu Setia Dewi; Ketut Sudarmini; Ida Ayu Agung Idawati (Warmadewa Management and Business Journal (WMBJ), 2023)
The purpose of this study was to determine and analyze the effect of work motivation, work history, and education on teacher performance. The survey was conducted at the Bali Dewata Health College, using a sample of 36 respondents who selected using a saturated sampling technique. All data obtained from distributing questionnaires can be used and then analyzed using multiple regression and hypothesis testing (t-test and f-test). The results were, (1) work motivation, work experience and education had a positive and significant effect on teacher performance at the Bali Dewata High School of Health. (2) Work motivation had a significant effect on teacher performance at the Bali Dewata High School of Health. This proved to have a positive and significant effect on teacher performance. This means that the higher the motivation to work, the better performance of teachers at the Bali Dewata Health College. (3) Work history has a positive and significant effect on teacher performance at the Bali Dewata Health College. This means that the better the professional experience, the better the performance of the Bali Dewata Health College teachers. (4) Education has a positive and significant effect on teacher performance at the Bali Dewata Health College. In other words, the more training, the better the performance of teachers at the Bali Dewata Health College.